Effects of simulated nibbling intensity on growth and physiological characteristics of Caragana tibetica - Liang, Yumei; He, Minghui; Jia, Ruiting; Tian, Qi; Chen, Jiahuan; Li, Min (Frontiers in Plant Science, 2025)
As one of the typical sand-fixation and soil and water conservation shrub species in the desert steppe, the effects of simulated nibbling intensity on the growth and physiological characteristics of Caragana tibetica are unclear. To solve the problem, in this paper, Caragana tibetica with complete configuration, good growth status, close location, the same terrain, and basically consistent morphological structure in the test area were selected as the research objects. The artificial pruning method was adopted to simulate different intensities of animal nibbling. The field in-situ sampling and indoor index determination methods were used to determine its growth and physiological characteristics, so as to clarify the growth and physiological response characteristics of Caragana tibetica to simulated nibbling. The results showed that: (1) The higher the nibbling intensity, the greater the number of new branches and the length of new branches. (2) Different simulated nibbling intensities had significant effects on the physiological characteristics of Caragana tibetica, whose effects are through antioxidant enzymes, osmoregulatory substances, and malondialdehyde. (3) During the whole growing season of Caragana tibetica, the value of physiological characteristics increased first and then decreased, reaching the maximum value in July. (4) The growth characteristics and physiological characteristics of Caragana tibetica have different degrees of correlation. This paper clarifies the impact of simulated nibbling intensity on the growth and physiological characteristics of Caragana tibetica, which can provide an important theoretical basis and practical significance for promoting the sustainable development and utilization of the desert steppe.